Effects of artepillin c on model membranes displaying liquid immiscibility - Pazin, W. M.; Vilanova, N.; Voets, I. K.; Soares, A. E.E.; Ito, A. S. (FapUNIFESP (SciELO), 2019)
It has been hypothesized that the therapeutic effects of artepillin C, a natural compound derived from Brazilian green propolis, are likely related to its partition in the lipid bilayer component of biological membranes. To test this hypothesis, we investigated the effects of the major compound of green propolis, artepillin C, on model membranes (small and giant unilamelar vesicles) composed of ternary lipid mixtures containing cholesterol, which display liquid-ordered (lo) and liquid-disordered (ld) phase coexistence. Specifically, we explored potential changes in relevant membrane parameters upon addition of artepillin C present-ing both neutral and deprotonated states by means of small angle X-ray scattering (SAXS), differential scanning calorimetry (DSC), and confocal and multiphoton excitation fluorescence microscopy. Thermotropic analysis obtained from DSC experiments indicated a loss in the lipid cooperativity of lo phase at equilibrium conditions, while at similar conditions spontaneous formation of unilamellar vesicles from SAXS experiments showed that deprotonated artepillin C preferentially located at the surface of the membrane. Time-resolved experiments using fluorescence microscopy showed that at doses above 100 mM, artepillin C in its neutral state interacted with both liquid-ordered and liquid-disordered phases, inducing curvature stress and promoting dehydration at the membrane interface.
Keywords: Artepillin C; DSC; Giant unilamellar vesicles; Green propolis; Model membranes; SAXS